Lower protein and higher carbohydrate intake are related with altering metabolic syndrome components in elderly women: A cross-sectional study - Nabuco, Hellen C.G.; Tomeleri, Crisieli M.; Sugihara Junior, Paulo; dos Reis Fernandes, Rodrigo; Cavalcante, Edilaine F.; Antunes, Melissa; Burini, Roberto Carlos [UNESP]; Venturini, Danielle; Barbosa, Décio S.; Silva, Analiza Mônica; Cyrino, Edilson S. (Elsevier, 2018)
Background Metabolic Syndrome (MetS) is an energy-disturbance disease associated with insulin resistance. Hence, the intake of energy-rich macronutrients might affect some MetS components. The aim of this study was to explore the association of ingested macronutrients with MetS components in older women. Methods A cross sectional study was conducted in 245 older women (≥60 years). Whole-body dual-energy X-ray absorptiometry was used to assess total body fat, percentage body fat (absolute and relative), and skeletal muscle mass. Venous blood samples were collected after a 12 h fasting to determine glucose, high-density lipoprotein (HDL-c), and triglycerides. Anthropometric measurements and resting blood pressure were also evaluated. Food consumption was assessed through the 24-hour dietary recall method, and the macronutrients were distributed by tertiles of consumption. The Student t-test, Mann–Whitney U test, and logistic regression analysis were used for statistical analysis. Results The MetS and non-MetS groups demonstrated similar food-energy intake and fat consumption. The MetS group presented lower protein and higher carbohydrate intake than the non-MetS group. Individuals in the lowest protein intake (<0.72 g/kg/d) had greater odds of presenting abdominal obesity and impaired glucose levels. Higher consumption of carbohydrates was associated with lower HDL levels and higher hypertriglyceridemia. The chances of having MetS were increased by three times when ingesting either a low protein or high carbohydrate diet. Conclusion Either high carbohydrate or low protein intake would be risk factors for altering MetS components and the presence of MetS in elderly women.
Keywords: Aging; Body composition; Dietary intake; Hyperglycemia; Metabolic diseases